The effectiveness of PROMPT therapy for children with cerebral palsy - Ward, Roslyn (Curtin University, 2012)
The purpose of this study is to evaluate the effectiveness of a motor speech treatment approach (PROMPT) in the management of motor-speech impairment in children with cerebral palsy. Two main objectives were addressed: (1) to evaluate changes in speech intelligibility and, (2) evaluate changes in kinematic movements of the jaw and lips using three dimensional (3D) motion analysis.A single subject multiple-baseline-across-participants research design, with four phases: Baseline (A1), two intervention phases (B and C) and maintenance (A2), was implemented.Six participants, aged 3-to-11-years (3 boys, 3 girls) with moderate to severe speech impairment were recruited through The Centre for Cerebral Palsy, Western Australia (TCCP). Inclusion criteria were: diagnosis of cerebral palsy, age 3 – 14 years, stable head control (supported or independent), spontaneous use of at least 15 words, speech impairment ≥1.5 standard deviations, hearing loss no greater than 25dB, developmental quotient ≥70 (Leiter-Brief International Performance Scale R) and no previous exposure to PROMPT. Thirteen typically-developing peers were recruited to compare the trend of kinematic changes in jaw and lip movements to those of the children with cerebral palsy.Upon achievement of a stable baseline, participants completed two intervention phases both of 10 weeks duration. Therapist fidelity to the PROMPT approach was determined by a blinded, independent PROMPT Instructor.Perceptual outcome measures included the administration of weekly speech probes, containing trained and untrained vocabulary at the two targeted levels of intervention plus an additional level. These were analysed for both perceptual accuracy (PA) and the motor speech movement parameter. End of phase measures included: 1. Changes in phonetic accuracy as measured using a measure of percentage phonemes correct; 2. Speech intelligibility measures, using a standardised assessment tool; and 3. Changes to activity/participation using the Canadian Occupational Performance Measure (COPM).Kinematic data were collected at the end of each study phase using 3D motion analysis (Vicon Motus 9.1). This involved the collection of jaw and lip measurements of distance, duration and velocity, during the production of 11 untrained stimulus words. The words contained vowels that spanned the articulatory space and represented motor-speech movement patterns at the level of mandibular and labial-facial control, as classified according to the PROMPT motor speech hierarchy.Analysis of the speech probe data showed all participants recorded a statistically significant improvement. Between phases A1-B and B-C 6/6 and 4/6 participants respectively, recorded a statistically significant increase in performance level on the motor speech movement patterns (MSMPs) targeted during the training of that intervention priority (IP). The data further show that five participants (one participant was lost to follow-up) achieved a statistically significant increase at 12- weeks post-intervention as compared to baseline (phase A1).Four participants achieved a statistically significant increase in performance level in the PA of the speech probes of both IP1 and IP2 between phases A1-B. Whilst only one participant recorded a statistically significant increase in PA between phases BC, five participants achieved a statistically significant increase in IP2 between phases A1-C. The data further show all participants achieved a statistically significant increase in PA on both intervention priorities at 12-weeks post-intervention. All participants recorded data that indicated improved perceptual accuracy across the study phases. This was indicated by a statistically significant increase in the percentage phonemes correct scores F(3,18) = 5.55, p<.05.All participants achieved improved speech intelligibility. Five participants recorded an increase in speech intelligibility greater than 14% at the end of the first intervention (phase B). Continued improvement was observed for 5 participants at the end of the second intervention (phase C).